Application of Learning Strategies Contextual Teaching and Learning (CTL) in Improving Student Learning Outcomes in Ancient and Modern Human Materials - Suwarno Suwarno (Metafora: Education, Social Sciences and Humanities Journal, 2021)
The purpose of this classroom action research is to know the students' learning mastery. This study is limited to the subjects of history. The subjects of the study were students of Class X IPS-1 SMA Negeri 1, Kota Mojokerto semester of the academic year 2017/2018 which amounted to 36 students. This research is a class action research (action research). The learning tools used in this study include syllabus and lesson plans. The research instrument consists of observation / observation sheet of student and teacher activity and student response questionnaire. The result of the research shows that learning with Contextual Teaching Learning (CTL) strategies  is quite effective which is marked by the increase of the percentage of students' learning result completion by classical from 70.56% (round 1), 75.53% (round 2) and 86.67% (round 3).